Contemporary paradigms for cholinergic ligand design guided by biological structure - Taylor, Palmer (2004)
The identification of the various nicotinic receptor subtypes, when coupled with the recent development of three-dimensional structures of surrogate extracellular receptor domains, offers new opportunities to design nicotinic ligands. Conformation and fluctuations in receptor structure are critical to ligand selectivity, and we present here how a flexible receptor template can be used in the development of selective ligands affecting cholinergic neurotransmission.